Marine Tourism in the South East of Russia: The State and Development Tendencies - Derkacheva, Ludmila Nikolaevna; Kosolapov, Alexander Borisovish; Galenko, Elena Vasilevna; Makartseva, Elena Vladimirovna (International Review of Management and Marketing, 2016)
The article deals with history of emergence of marine tourism in the South East of Russian Federation. It analyzes contemporary approaches to arrangement of marine tourism, defines the priority kinds of sea holidays, emphasizes problems of cruise carriages and outlines the main trends in the development of marine tourism. Keywords: marine tourism, coast of Peter the Great Bay, expedition cruise tourism, yachting, Primorsky Region. JEL Classifications: F5, L9, Z3